Common Ground : Melodramas of 9/11 - Cvek, Sven (2010)
The article deals mainly with Jonathan Safran Foer's novel "Extremely Loud and Incredibly Close, "a post-traumatic family drama that efficiently registers the main modalities of mourning and communal consolidation after the September 11, 2001 terrorist attack on the United State. The article also offers a discussion of the dominant generic frameworks active in the national response to the terrorist attacks, most notably melodrama.
Projekt MZOS
ENG